2017
DOI: 10.1007/s11356-017-0989-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rice straw mulching on N2O emissions and maize productivity in a rain-fed upland

Abstract: In the hilly areas of southern China, uplands and paddies are located adjacent to each other. Using rice straw as mulch for upland soil may improve crop production and partially replace chemical fertilizers, which may mitigate NO emissions. A field experiment was conducted to investigate the potential of rice straw mulching for mitigating NO emissions and increasing crop production. The treatments included no mulching (CK), 5000 kg ha of straw mulching (SM5), and 10,000 kg ha of straw mulching (SM10). Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In addition, crop residues such as straw incorporation are widely applied in paddy soil fields to improve soil quality and fertility in China. It has been suggested that straw returning in paddy soil can remarkably enhance soil organic carbon stock and has distinct effects on greenhouse emission and soil microbial community through altering soil physical condition and soil C/N (Yan et al, 2013;Lu et al, 2015;Wang et al, 2018a;Wu et al, 2018;Yao et al, 2018). However, the influence of straw returning on DNRA process is rarely estimated.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, crop residues such as straw incorporation are widely applied in paddy soil fields to improve soil quality and fertility in China. It has been suggested that straw returning in paddy soil can remarkably enhance soil organic carbon stock and has distinct effects on greenhouse emission and soil microbial community through altering soil physical condition and soil C/N (Yan et al, 2013;Lu et al, 2015;Wang et al, 2018a;Wu et al, 2018;Yao et al, 2018). However, the influence of straw returning on DNRA process is rarely estimated.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the difference between SOC and TN, the high C/N of straw could be one major reason. When straw is added to soil, microorganisms use up available nitrogen to decompose the straw, temporarily slowing the short-term increase in TN [51]. This shows that the improvement effect of straw return on different indicators is influenced by their characteristics.…”
Section: Straw Return Overall Effectsmentioning
confidence: 96%
“…However, the SOC will decrease rapidly once the continuous straw return stops due to the introduction of numerous labile carbon compounds and the acceleration of "priming effects" [41]. In a rain-fed upland, the practice of long-term rice straw return was used to increase maize productivity; although compared with the control, straw return significantly increased maize yield, a year-on-year comparison within the straw return group showed a decline over the years [51]. Jiang et al and Wang et al found that straw return significantly increased crop yield after continuous return for 5 years [54,55].…”
Section: Straw Durationmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrous oxide production can be mitigated using mulches (e.g., rice straw) and by minimizing fertilizer requirements in the soil. It is evident that soil water-filled pore spaces play an important role in N 2 O emissions in the field; therefore, altering nitrogenous fertilizer with mulch can contribute to N 2 O mitigation ( Wu et al., 2018 ). Intercultural operations, such as mulching, can also reduce O 3 -induced losses.…”
Section: Mitigation Of O 3 Stress In Cropsmentioning
confidence: 99%